Penggunaan Metode Direction Finder Triangulation Untuk Mempermudah Komunitas Radio Dalam Melacak Posisi Sinyal Radio - Muhammad Ikhsan; Neilcy Tjahjamooniarsih; Dedy Suryadi (ARMADA : Jurnal Penelitian Multidisiplin, 2025)
Direction Finder Triangulation is a method used to track the position of a radio signal source by utilizing a receiver equipped with directional antenna, requiring at least two refence sites. This method can assist radio communities such as The Indonesian Amateur Radio Organization (ORARI) in locationg radio signals, particularly during Fox Hunting activities. This paper aims to understand how the Direction Finder Triangulation method is use and to identify the parameters that influence the accuracy. The research applies the Direction Finder Triangulation method using several tools, including two Handy Talky as transmitter-receiver, 3 element Yagi Antenna for signal tracking, and Avenza Maps for measurement and mapping of angle points at each reference location. The research was conducted around Tanjungpura University area and involved 10 trials at distances ranging from an initial 100 meters to final 1000 meters. The results show that the accuracy of the Direction Finder Triangulation method exceeds 90%, with the lowest accuracy recorded at 91.30% and the highest at 99.72%. The farther the distance between transmitter and receiver, the weaker received signal strength becomes, and weaker signal strength leads to reduced accuracy. Direction Finder Triangulation method can facilitate radio communities in tracking radio signal positions and can also be used to locate illegaly operating transmitters.